Empowering student learning through Tablet PCs: A case study - Li, Sandy C; Pow, Jacky WC; Wong, Emily ML; Fung, Alex CW (Education and Information Technologies, 2010)

Increasing Interactivity in Distance Educations: Case Studies Bangladesh and Sri Lanka - Andersson, Annika; Hatakka, Mathias (Information Technology for Development, 2010)

Slum dwellers' response to free primary education: a case study of Kibera slum, Nairobi - Njeru, Caroline N. (University of Nairobi, 2010)

Effective Use of Assistive Technologies for Inclusive Education in Developing Countries: Issues and challenges from two case studies - Grönlund, Åke; Lim, Nena; Larsson, Hannu (International Journal of Education and Development using ICT, 2010)
Developing countries face many obstacles in the process of implementing inclusive education (IE). Effective use of assistive technologies (AT) can help governments in developing countries achieve inclusive education by helping children with disabilities in schools. Despite the importance and positive impact of AT, prior research on the use of AT in inclusive education especially in developing countries is limited. To fill the research gap in this area, this paper investigates the research question of, How can AT be effectively used for IE in developing countries? To address this question,...
Keywords: ⛔ No DOI found

Early Childhood Longitudinal Study, Kindergarten Class of 1998–99 (ECLS) correct theta scores for the kindergarten through eighth grade data collections errata - Chapman, Chris (National Center for Education Statistics, 2010)
Find information about and locate all publications and data products on education information from the National Center for Education Statistics--NCES--. In most cases you may also browse the content of publications or download data files.

E-learning in secondary Schools in Kenya: A Case of the NEPAD E-schools - Ayere, Mildred; Odera, F; Agak, John (Educational Research and Reviews, 2010)
The New Partnership for Africa's Development (NEPAD) schools were set up as centres of excellence in Information and Communication Technology (ICT) integration, so that other schools could copy their model in e-learning. It was for this reason that they were provided with computers, e-materials, internet appliances and trained personnel. But to gauge their levels of success as e-learning centres there was need to compare them to other schools offering ICT education in Kenya. It was for this reason that this study compared the application of the e-learning in NEPAD and non-NEPAD schools in Kenya. Specifically, the study: Identified significant differences in levels of integration of ICT in curriculum subjects; surveyed the differences in use of e-materials in education research; examined availability of e-libraries; identified significant differences in academic performance of NEPAD and non-NEPAD schools attributed to e-learning. The study used a combination of an exploratory approach using descriptive survey and ex-post-facto design. It was carried out in six of the eight provinces in Kenya, where the NEPAD schools are located. It targeted 1600 form four students from 35 secondary schools involved in ICT education (NEPAD schools included). Saturated sampling was used for the six NEPAD schools while six non-NEPAD schools were selected through simple random sampling. The sample consisted of three officials from the ministry of education, twelve principals and twelve heads of ICT department (HODs), and 570 of the form four students. The main data collection instrument was the questionnaire; administered to the students, the principals, and the HODs. The interview schedule was administered to the ministry of education personnel while an observation checklist was used as a confirmatory tool. Analysis was done using both descriptive and inferential statistics. The study found that, there was a significant difference in the application of e-learning in NEPAD and non-NEPAD schools. Based on these findings, it was recommended that schools involved in ICT education should intensify teacher facilitation and support teacher roles that are required in e-learning Key words: E-Learning, ICT integration, ICT education, new partnership for Africa's development (NEPAD).
Keywords: ⛔ No DOI found

Using School Performance Data to Drive School and Education District Office Accountability and Improvement: The Case of Ghana - Prew, Martin; Quaigrain, Kenneth (Educational Management Administration & Leadership, 2010)
Distance-education delivery through interactive television (ITV) is an effective means of providing instruction to learners. There are many advantages, such as the ability to provide immediate feedback and personal participation. To be effective, however, ITV requires structured planning and development, making the use of instructional design principles imperative. The following recommendations are made for training teachers about ITV: (1) provide an overview of the technology and how it works; (2) provide hands-on guided practice; (3) incorporate effective elements of instruction; (4) conduct periodic follow-up inservice training; (5) train with teachers who volunteer; (6) establish the amount of time needed to prepare and teach ITV courses; (7) provide experiences with other faculty members; (8) incorporate strategies for adding visual components to audio courses; and (9) use strategies that encourage group cohesion and student motivation. Teachers must adapt instruction to meet the varied needs of students, as both teachers and students adjust to the demands of the medium. (SLD)
Keywords: Delivery Systems; Distance Education; Educational Planning; Educational Technology; Educational Television; Feedback; Graduate Study; Higher Education; Information Transfer; Instructional Design; Instructional Effectiveness; Interactive Television; Student Motivation; Teacher Attitudes; Teacher Education; Teaching Methods; Technological Advancement; Telecourses; Training; search_string_27b

eSkwela project - eSchool for out-of-school youths and adults, Philippines - Kamei, M (2010 International Conference on Technology for Education, 2010)
There are 774 million non-literates globally (UNESCO, 2009) and there is the acute problem of illiteracy grave in South Asian region. The paper discusses the implementation of eSkwela project as Alternative Learning System (ALS) in Philippines. The initiative responds directly to a national development priority to bring elearning opportunities and Information Communication Technology (ICT) for learning resources to mobile teachers / instructional managers and out-of-school learners in the Philippines. The paper assesses how the eSkwela project initiatives have provided opportunities for remote and elearning, blended learning and how Alternative Learning System (ALS) has been supported by innovative use of ICT for content development. It presents a macro view, case study of the strategic approach, design, challenges and successes faced by the eSkwela project which is still a work in progress. Rudiments in ICT for Education for citizens to attain the new-age literacy and lifelong learning opportunities are also evaluated.
Keywords: Aging; Alternative Learning System (ALS); Blended Learning; Collaboration; Communications technology; Computer science education; Educational institutions; Educational products; Electronic learning; Learning Management System (LMS); Learning systems; Space technology; Technology management; Virtual Learning Environment (VLE); ⛔ No INSPIRE recid found

Toward a Successful Plan for Educational Technology for Low-income Communities: A Formative Evaluation of One Laptop Per Child (OLPC) Projects in Nigeria and Ghana - Ezumah, Bellarmine Anthonia (Howard University, 2010)
Copious educational technology projects have been implemented in several low-income communities by multilateral institutions, individuals, and governmental agencies. Statistics show that the majority of these initiatives fail to accomplish their objectives, thereby wasting colossal amounts of money, talent, and resources. Scholars aver that poor planning and implementation are the major deterrents to a successful technology project (Flagg, 1990; Osin, 1998; Warschauer, 2006). Responding to this problem, the current work seeks to provide a model for an effective plan for introducing educational technology that will yield a better result for elementary education. Using as a case the One Laptop Per Child (OLPC), a computer program initiated by MIT professor Nicholas Negroponte to enhance education in low-income communities, this study specifically evaluates the planning and implementation strategies employed in the OLPC pilot projects in Abuja, Nigeria and Accra, Ghana. A participatory research approach was employed and qualitative data were collected in situ using in-depth interviews and questionnaires with parents, school leaders, students, public educational officials, community leaders, subject-matter experts, and OLPC personnel involved in the OLPC projects at LEA Galadima Primary School, Abuja, Nigeria and Kanda Primary School, Accra, Ghana. The project under study is a Western initiative; thus, the dominant paradigm of development communication theory and its alternative, the participatory action research, were employed as the theoretical framework. Results from the study allowed the researcher to posit a model toward a better plan for educational technology adoption in low-income communities. Some highlights include the need for every country to establish a standardized educational technology objective, ability to raise funds enough to keep it going, the need to incorporate local materials as major content, and acknowledging input of local experts, and the teachers' role in the entire process.
Keywords: Applied sciences; Communication and the arts; Constructivist pedagogy; Education; Educational technology; Formative evaluation; Ghana; Low-income; Nigeria; One Laptop Per Child; ___working_potential_duplicate